2017
DOI: 10.1186/s13059-017-1167-5
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insights into divergence and dual domestication of cultivated allotetraploid cottons

Abstract: BackgroundCotton has been cultivated and used to make fabrics for at least 7000 years. Two allotetraploid species of great commercial importance, Gossypium hirsutum and Gossypium barbadense, were domesticated after polyploidization and are cultivated worldwide. Although the overall genetic diversity between these two cultivated species has been studied with limited accessions, their population structure and genetic variations remain largely unknown.ResultsWe resequence the genomes of 147 cotton accessions, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
133
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(141 citation statements)
references
References 63 publications
7
133
1
Order By: Relevance
“…Therefore, the genetic variation was not mainly caused by TE insertions. In addition, SNP frequency in LS and core regions was calculated according to resequencing data using 58 G. hirsutum accessions and 70 G. barbadense accessions (Fang et al ., ; Wang et al ., ). It was found that SNP frequency was consistently higher in LS lncRNAs than core lncRNAs in all comparisons ( P ‐value < 2.2e‐16) (Figures c and S6).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the genetic variation was not mainly caused by TE insertions. In addition, SNP frequency in LS and core regions was calculated according to resequencing data using 58 G. hirsutum accessions and 70 G. barbadense accessions (Fang et al ., ; Wang et al ., ). It was found that SNP frequency was consistently higher in LS lncRNAs than core lncRNAs in all comparisons ( P ‐value < 2.2e‐16) (Figures c and S6).…”
Section: Resultsmentioning
confidence: 99%
“…A new cotton single‐nucleotide polymorphism (SNP) chip, the CottonSNP80K array, covering the genome of upland cotton, was successfully developed based on the sequencing of TM‐1 (Zhang et al ) and the re‐sequencing of 100 different cultivars in upland cotton with 5× coverage, on average (Fang et al ). The array contains the following information: (i) 77,774 SNP loci and a genotype accuracy of ≥ 99.12%; (ii) filtered SNPs in repeat regions; (iii) no other SNPs or insertions or deletions (InDels) in the 50 base pairs (bp) flanking the SNP sites; (iv) heterozygosity rates of ≤ 15%; (v) SNPs in gene regions have Illumina design scores of ≥ 0.7; and (vi) SNPs in intergenic regions have Illumina design scores of ≥ 0.9 (Cai et al ).…”
Section: Introductionmentioning
confidence: 99%
“…For determining the entire set of genes with their functions, genome sequencing of an organism is an important prerequisite resource. At present, the sequenced and re‐sequenced genomes of diploid and allotetraploid (Fang et al ., ,; Li et al ., , ; Liu et al ., ; Paterson et al ., ; Wang et al ., ; Yuan et al ., ; Zhang et al ., ) cotton have been available, which presents valuable information for cotton genomes. However, large knowledge gaps still persist as compared to Arabidopsis and rice, concerning with the molecular regulation of the fundamental biological processes.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In addition, re‐sequencing the genome for which there is a reference genome available permits exploration of the association between sequence variations. Recent comprehensive genome assessment by genome‐wide re‐sequencing of 34 (Page et al ., ), 318 (Fang et al ., ), 147 (Fang et al ., ) and 352 (Wang et al ., ) cotton accessions represented extensive collections in order to identify genome regions that are signature of selection. These studies provide new genomic resources that significantly advance molecular breeding in cotton.…”
Section: Cotton Genome Sequencing: Progress and Implicationsmentioning
confidence: 99%